2021
DOI: 10.32539/bsm.v5i4.366
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors with the Degree of Pelvic Organs Prolapse at Dr. Mohammad Hoesin General Hospital Palembang

Abstract: Background. Pelvic organ prolapse (POP) is a condition in which one or more pelvic organs (consisting of the uterus, vaginal cuff, bladder, intestines, and rectum) or more are still in or out of the vagina. Risk factors that influence the incidence of POP consist of obstetric risk factors (number of parity and birth method) and non-obstetric risk factors (age, menopause, BMI, comorbid disease, and hypertension). The purpose of this study was to analyze the risk factors associated with the degree of POP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Vaginal birth and parity may significantly increase the risk of POP later in life. There is study found that most women with POP (80%) had more than two parities [12]. Similarly, Putra et al also found a higher incidence of POP in multiparous women (68.5%) [13].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Vaginal birth and parity may significantly increase the risk of POP later in life. There is study found that most women with POP (80%) had more than two parities [12]. Similarly, Putra et al also found a higher incidence of POP in multiparous women (68.5%) [13].…”
Section: Discussionmentioning
confidence: 94%
“…At the age of 80 years, it was reported that the risk for women in the United States to undergo at least one POP operation was 6.3% with the risk of undergoing reoperation reaching 30% [10]. Other studies in Indonesia also reported that almost all POP patients were aged older than 40 years old [5], [12]. The estrogen levels tend to decrease in older women (aged more than 40 years until before menopause) so that the production and degradation of extracellular matrix proteins that maintain tissue stability and prevent collagen degradation will also decrease, causing weakness of the pelvic floor muscles which later manifests 5-10 years post-menopause.9 After menopause, the function of the ovaries and the estrogen levels will decrease even further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation